P169 Activated effector T cells co-expressing multiple inhibitory receptors are enriched in the tumor immune microenvironment of HGSOC expressing high and uniform WT-1 antigen. (1st November 2019) - Bergamini, A; Tassi, E; Wignall, J; Ruggiero, E; Bocciolone, L; Candiani, M; Potenza, A; Manfredi, F; Taccagni, G; Scalisi, F; Doglioni, C; Schultes, B; et al.
Abstract : Introduction/Background: In high grade serous ovarian cancer(HGSOC), the association between tumor-infiltrating lymphocytes(TILs)and survival suggests a role for T cell immune surveillance. Despite this, initial attempts with PD1 checkpoint blockade and adoptive T-cell therapy(ACT) had limited efficacy. This highlights the need to characterize the phenotype of TILs and to find new potential tumor-associated antigens.Wilms tumor-1(WT-1)expression showed a prognostic significance in HGSOC, making it an interesting target.To identify molecules potentially relevant for HGSOC immunotherapy, we evaluated the expression of WT-1 and the pattern of inhibitory receptors(IRs)in TILs. Methodology: Peripheral blood(PB), tumor and ascites were retrieved from HGSOC patients admitted for primary surgery.WT-1 expression and immune infiltrate were characterized on 34 specimens by immunohistochemistry (IHC) for lineage markers and inhibitory molecules.T cells isolated from tumor, ascites and PB of 14 patients were also characterized by flow cytometry for the expression of lineage and memory markers (CD3, CD4, CD8, CD45RA, CD62L, CD95), inhibitory molecules (PD1, CTLA-4, LAG-3, TIGIT, TIM-3, 2B4, GITR, KLRG1, CD39, CD160)and the activation marker CD137. Results: WT1 was almost uniformly expressed, with 76% of cases showing high WT1 expression in the majority of tumor cells. 6% of cases were immune desert; all other cases displayed a wide range of immune cell density, dominated by T lymphocytes and macrophages. Intratumoral T cells(ITTCs), mainly CD8, were present in 88.2% of samples. PD-1, LAG-3 and TIM-3 were expressed by 61.9%, 61.7% and 61.7% of ITTCs. PD-L1 was expressed by neoplastic cells and immune cells in 40% and 82.3% of samples.Flow cytometry confirmed the expression of several IRs.Compared with PB and ascites, TILs were enriched in effector memory lymphocytes and in cells coexpressing PD-1, CD39 and CD137. Conclusion: WT-1 is a potential target for ACT in HGSOC, which is infiltrated by antigen-experienced T lymphocytes displaying features of activation and partial exhaustion. Disclosure: Nothing to disclose.